2020
DOI: 10.23887/jisd.v4i3.25376
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Reading Interests and Learning Motivation Toward Science Learning Outcomes

Abstract: The low reading interests and learning motivation are the main problems in this study. That is due to the lack and support of families, schools, and communities to increase reading interests and learning motivation. This study aimed to determine the relationship of reading interests and learning motivation with the learning outcomes of science class V of primary school (elementary school). This type of research was ex-post facto research. The population of this study was 187 people. The sample was determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
1
5
0
1
Order By: Relevance
“…It is shown by the interview result from one interviewee who said that students fluent in reading and show high interest in reading have better grades than those who were not. This shows the similar result with previous research that showed there was significant connection between reading interests and grades, especially for science class (Retariandalas, 2017;Wahyuni et al, 2020). Even though this research was not comparing science grade with reading interests in particular, researchers also find that students with reading interests could more easily understand science materials they got.…”
Section: Discussionsupporting
confidence: 87%
“…It is shown by the interview result from one interviewee who said that students fluent in reading and show high interest in reading have better grades than those who were not. This shows the similar result with previous research that showed there was significant connection between reading interests and grades, especially for science class (Retariandalas, 2017;Wahyuni et al, 2020). Even though this research was not comparing science grade with reading interests in particular, researchers also find that students with reading interests could more easily understand science materials they got.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the results of other studies, motivation has a linear relationship to learning outcomes. The higher the student's motivation, the higher the learning outcomes, both Integrated Science and Social Sciences (Wahyuni et al, 2020).…”
Section: The Influnce Of Charta Media On Coastal Students Motivationmentioning
confidence: 99%
“…Kegiatan pembelajaran IPA yang terfokus pada materi yang disampaikan oleh guru menyebabkan siswa kurang antusias dalam pembelajaran IPA. Pembelajaran IPA seperti, mengakibatkan siswa kurang konsentrasi dalam menyimak penjelasan guru dan siswa kesulitan dalam menemukan pada materi yang disampaikan, hal ini dikarenakan pembelajaran tidak menggunakan media pembelajaran (Astuti et al, 2020;Wahyuni et al, 2020;Oktafiani et al, 2020). Selanjutnya diadakan pengamatan kegiatan pembelajaran IPA yang dilaksanakan di SD Negeri 4 Banyuasri, kegiatan pembelajaran pada di masa pandemi ini masih terdapat beberapa kendala; kurangnya penggunaan media pembelajaran yang dapat membantu siswa dalam menerima materi pembelajaran, pelaksanaan kegiatan pembelajaran IPA kurang menggunakan model pembelajaran yang inovatif, kegiatan pembelajaran hanya sebatas mengirimkan materi pembelajaran dan tugas sehingga ketertarikan siswa terhadap muatan pelajaran IPA masih kurang, dan siswa kesulitan memecahkan masalah yang berkaitan muatan pelajaran IPA yang terjadi di kehidupan sehari-hari serta terdapat nilai hasil belajar siswa yang diperoleh dari Penilaian Akhir Semester (PAS) di bawah KKM pada muatan pelajaran IPA.…”
Section: Pendahuluanunclassified